Limnological Studies Related to Physico-Chemical Characteristics of Water of Santragachi and Joypur Jheel, W.B., India - Patra, A.; Santra, K.B.; Manna, C.K. (Our Nature, 2011)
The present study deals with the seasonal limnological investigation related to physico-chemical characteristics of water of the Santragachi and Joypur Jheel, West Bengal, India. Besides temperature and meteorological data, 17 limnological parameters were tested following standard methods at 3 sampling sites/stations of each Jheel. The physico-chemical parameters (transparency, pH, DO, BOD, COD, free CO2, total alkalinity, conductivity, CaCO3, TSS, TDS, Chloride, Ammonia, Nitrite, Nitrate, Phosphate, etc.) showed distinct temporal or seasonal variation in both the Jheels. Higher nutrient contents (nitrate, phosphate) are present in Santragachi Jheel. This finding also signifies eutrophication/higher trophic level. Water transparency, dissolved oxygen, BOD, total alkalinity, conductivity, CaCO3 hardness, TSS, nitrate and phosphate was correlated with various physico-chemical parameters in both the Jheels. The physico-chemical characteristics of water of the two Jheels revealed the poor water quality in Santragachi Jheel than the Joypur Jheel. These characteristics showed maximum contamination of water due to sewage effluents in Santragachi Jheel. The two years (February, 2000 - January, 2002) survey reflects higher degree of pollution in Santragachi Jheel. DOI: 10.3126/on.v8i1.4328